SMALL CELL LUNG CARCINOMA WITH CORONARY ARTERY DISEASE AND SUPERIOR VENA CAVA SYNDROME IN NON SMOKER, ELDERLY WOMAN PATIENT : A CASE REPORT - I Gede Arya Yoga Dharma Wiguna; Bagus Agung Arya Dharma Pramana Dwi Sutanegara; I Putu Angga Manik Pratama; Luh Gede Janny Resista Yani; Ni Made Dwita Yaniswari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Small cell lung carcinoma (SCLC) is an aggressive form of lung cancer typically associated with tobacco exposure; however, a subset of patients develops SCLC without a history of smoking. This case report describes an elderly non-smoking female with SCLC complicated by coronary artery disease and superior vena cava (SVC) syndrome treated at Wangaya General Hospital. The patient presented with progressive dyspnea, facial swelling, and productive cough. Thoracic computed tomography revealed a large right lung mass compressing both the superior and inferior vena cava, accompanied by pleural effusion. Histopathological examination confirmed SCLC. The patient also had underlying coronary artery disease and electrolyte disturbances. Clinical and imaging findings were consistent with advanced-stage disease (T4N3M1) complicated by SVC syndrome. This case highlights a non-smoker SCLC phenotype with vascular compression and cardiovascular comorbidity, suggesting potential oncogenic mechanisms beyond smoking exposure. The coexistence of coronary artery disease and SVC obstruction posed challenges in clinical management, emphasizing the importance of individualized treatment strategies. Non-smoker SCLC remains underrepresented in the literature despite its increasing incidence and distinct biological characteristics. In conclusion, non-smoking–related SCLC with concurrent cardiovascular disease and SVC syndrome presents significant diagnostic and therapeutic challenges, and further documentation is essential to improve clinical understanding and guide future management approaches.